CHARACTERISTICS OF HYDRAULIC JUMP ON ROUGH MINOR BED IN A RECTANGULAR COMPOUND CHANNEL. - Djamaa, W.; Lacheheb, S.; Ghomri, A. (Journal of Fundamental and Applied Sciences, 2021)
A hydraulic jump is a characteristic phenomenon in open channel flow, Downstream of block ramps or rock chutes a hydraulic jump can occur over a rough bed with great energy dissipation. This paper analyses the hydraulic jump that occurs in homogeneous rough minor beds in rectangular compound channels. the parameters that influence the length of the jump were systematically investigated [24]. the analyses of the phenomenon were conducted using the general jump equation. the experimental data were elaborated in order to supply a new formulation of the general jump equation that accounts for the minor bed roughness. New formulas that satisfactorily agree with the experimental data are proposed. The results showed that rough beds can be used to dissipate the excess hydraulic jump energy instilling basins.